2018
DOI: 10.1038/s41598-018-33397-9
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between adipose-derived stem cells and bladder cancer cells

Abstract: Tissue engineering approaches offer alternative strategies for urinary diversion after radical cystectomy. Possible triggering of cancer recurrence remains, however, a significant concern in the application of stem-cell based therapies for oncological patients. Soluble mediators secreted by stem cells induce tissue remodelling effects, but may also promote cancer cells growth and metastasis. We observed a substantial increase in the concentration of IL-6 and IL-8 in the secretome of adipose-derived stem cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…Adipogenesis, as defined by the formation of adipocytes from stem cells [ 1 ], and the adipose tissue itself have drawn much attention at the onset of chronic inflammation in metabolic diseases, such as type 2 diabetes mellitus, cardiovascular diseases, and in several types of cancer [ 2 , 3 ]. Among the processes involved in the setting of these diseases, the adipose tissue secretome has been inferred to play a crucial paracrine regulatory role in brain cancer [ 4 ], prostate cancer [ 5 ], bladder cancer [ 6 ], breast cancer [ 7 ], and colon cancer [ 8 ]. Molecular links between central obesity and breast cancer have also been inferred to trigger oncogenic signaling pathways, including NFκB, JAK, STAT3, and AKT [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adipogenesis, as defined by the formation of adipocytes from stem cells [ 1 ], and the adipose tissue itself have drawn much attention at the onset of chronic inflammation in metabolic diseases, such as type 2 diabetes mellitus, cardiovascular diseases, and in several types of cancer [ 2 , 3 ]. Among the processes involved in the setting of these diseases, the adipose tissue secretome has been inferred to play a crucial paracrine regulatory role in brain cancer [ 4 ], prostate cancer [ 5 ], bladder cancer [ 6 ], breast cancer [ 7 ], and colon cancer [ 8 ]. Molecular links between central obesity and breast cancer have also been inferred to trigger oncogenic signaling pathways, including NFκB, JAK, STAT3, and AKT [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This re-programming of adipose cells provides the cancer cells with the substrates to fuel β-oxidation and the oncometabolites necessary for growth and invasion. In addition, adipose-derived stem cells (ASCs) seem capable of acquiring properties similar to those of cancer associated-fibroblasts in the TME [18] and promoting cancer cell proliferation, viability and invasiveness, as well as chemoresistance [19][20][21]. Nevertheless, the factors and mechanisms involved in this interaction still need to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…ASC secretion of two pro‐inflammatory cytokines IL‐8 and IL‐6, described below, was increased when cocultured with bladder cancer cells . This is believed to have played a role in the observed reduced extra cellular matrix adhesion, as well as increase in the cell viability, invasion, and migratory ability . Finally, ASCs have also been shown to increase gastric cancer cell growth, migration, and progression through the SDF‐1/CXCR4 axis .…”
Section: Ascs In Cancermentioning
confidence: 90%
“…However, one study by Tian et al found that S100A7, described above for its role in breast cancer proliferation and metastasis, has also been shown to enhance cell migration, invasion, metastasis and the epithelial to mesenchymal transition of cervical cancer . ASC secretion of two pro‐inflammatory cytokines IL‐8 and IL‐6, described below, was increased when cocultured with bladder cancer cells . This is believed to have played a role in the observed reduced extra cellular matrix adhesion, as well as increase in the cell viability, invasion, and migratory ability .…”
Section: Ascs In Cancermentioning
confidence: 96%